Validation of the Polish version of the Functional Oral Intake Scale against flexible endoscopic evaluation of swallowing and the International Dysphagia Diet Standardization Initiative Functional Diet Scale - Milewska, Magdalena; Jamroz, Barbara; Panczyk, Mariusz; Chmielewska-Walczak, Joanna; Czernicki, Tomasz; Dabrowska-Bender, Marta; Folwarski, Marcin; Szostak-Wegierek, Dorota (Frontiers in Nutrition, 2025)
IntroductionThe Functional Oral Intake Scale (FOIS) is a widely used instrument for assessing oral intake in dysphagic patients. Despite its frequent use, a validated version for the Polish population has been lacking.MethodsThis study aimed to validate the Polish adaptation of FOIS (FOIS-PL) by examining its concordance with Fiberoptic Endoscopic Evaluation of Swallowing (FEES) outcomes and the International Dysphagia Diet Standardization Initiative Functional Diet Scale (IDDSI-FDS) scores across patients with diverse clinical profiles. The primary outcome measures included the Penetration-Aspiration Scale (PAS) score from FEES, pharyngeal residue quantification, and IDDSI-FDS scores. A total of 302 participants with varying clinical conditions were recruited. The cohort included individuals with head and neck malignancies, cerebrovascular incidents, neuromuscular disorders, and other dysphagia aetiologies.ResultsPatients with gastroesophageal reflux disease and those post-thyroidectomy consistently exhibited oral food intake with a FOIS-PL score of ≥5. A strong inverse correlation was found between FOIS-PL scores and PAS scores (rho = −0.739; p < 0.001), indicating that reduced oral intake was associated with increased penetration or aspiration risk. Significant differences in FOIS-PL scores were evident across patient subgroups stratified by PAS severity (PAS ≤ 2, PAS 3–5, PAS > 5) and IDDSI levels. Lower FOIS-PL scores corresponded with more impaired swallowing safety (PAS > 5). The median FOISPL score was 5 for individuals with pharyngeal residue and 6 for those without (p < 0.001). Inter-rater reliability between evaluations conducted by a dietitian (FOIS I) and a speech-language pathologist (FOIS II) demonstrated high consistency (tau = 0.995; p < 0.001). Convergent validity was supported by strong correlations between FOIS-PL and IDDSI-FDS scores (FOIS I vs. IDDSI-FDS I: tau = 0.819; p < 0.001; FOIS II vs. IDDSI-FDS II: tau = 0.815; p < 0.001).ConclusionThe Polish version of the Functional Oral Intake Scale (FOIS-PL) is a valid and reliable tool for assessing oral intake in dysphagia. The findings demonstrate high accuracy, reliability, and validity, supporting its use across diverse clinical conditions.